2019
DOI: 10.1021/acsaem.8b01609
|View full text |Cite
|
Sign up to set email alerts
|

Collective Effect of Fe and Se To Improve the Thermoelectric Performance of Unfilled p-Type CoSb3 Skutterudites

Abstract: Filled skutterudites constitute an important class of efficient and stable thermoelectric materials for power generation; however, their commercialization has been hampered due to the usage of expensive rare-earth elements as “fillers” and the nonavailability of the efficient and compatible p-type counterpart. In view of this, we report a state-of-the-art thermoelectric figure of merit (ZT) in rare-earth-free p-type unfilled CoSb3 skutterudite co-doped with Fe and Se, synthesized using a facile process of arc-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…The calculated S and power factors are qualitatively comparable with experimentally measured values, although the quantitative alteration in the estimated and measured electronic properties is attributed to the defects generation during the synthesis process in the lattice. This may also be understood and attributed to the several approximations used in the theoretical calculations, such as constant relaxation time assumption and occurrence of synthesis defects induced atomic disorder, in a manner similar to observation made previously. ,, …”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The calculated S and power factors are qualitatively comparable with experimentally measured values, although the quantitative alteration in the estimated and measured electronic properties is attributed to the defects generation during the synthesis process in the lattice. This may also be understood and attributed to the several approximations used in the theoretical calculations, such as constant relaxation time assumption and occurrence of synthesis defects induced atomic disorder, in a manner similar to observation made previously. ,, …”
Section: Resultssupporting
confidence: 58%
“…For the pristine compound 4735 k points in IBZ were used, and for the alloys 595–624 k points were used. The other details of the calculations can be found in our previous work …”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither SiGe-20% SiMo nor Yb 13.5 La 0.5 ZnSb 11 manage to achieve ZT values above 0.9, with maximum values of 0.88 at 1273 K and 0.77 at 1213 K, respectively. Although Li et al (2019) found SiGe-20% SiMo performs almost 50% better than all other additions of SiMo to SiGe when it comes to electrical conductivity, the downfall of SiGe-20% SiMo is its high thermal conductivity over the entire temperature range [45]. It starts at 4.9 Wm −1 K −1 at 273 K, only dropping below 4 Wm −1 K −1 for the first time at 1100 K, and finishes at 3.9 Wm −1 K −1 at 1273 K. Although Yb 13.5 La 0.5 ZnSb 11 does not perform the best here, the maximum ZT of 0.77 recorded for this material is almost six times greater than the maximum value of 0.13 recorded when testing Yb 14 ZnSb 11 .…”
Section: Enhanced High-temperature Thermoelectric Materialsmentioning
confidence: 99%
“…A promising thermoelectric material can be formed by doping with Bi and then producing a Mg 3 Sb 1.8 Bi 0.2 /graphene nanosheet (GNS) nanocomposite with a mass ratio of 80:1. Mg 3 Sb 1.8 Bi 0.2 /GNS (80:1) was modelled here after an investigation by Bhardwaj et al (2015) found this material to have a ZT of 1.30 at 773 K [45]. The modelling carried out using COMSOL produced a similar ZT level of 1.34 at 773 K. However, Bhardwaj et al (2015) did not test at temperatures above 773 K, and when Mg 3 Sb 1.8 Bi 0.2 /GNS (80:1) was modelled using COMSOL between 773 K and 873 K the maximum ZT value recorded was 1.65 and the maximum efficiency was 22.23%, both at 873 K. Mg 2.69 Li 0.01 Cd 0.5 Sb 2 and Mg 2.9875 Na 0.0125 Sb 2 recorded maximum ZT values of 0.84 and 0.62 respectively, meaning they both struggle to compete with their magnesium counterpart Mg 3 Sb 1.8 Bi 0.2 /GNS (80:1).…”
Section: Enhanced Mid-temperature Thermoelectric Materialsmentioning
confidence: 99%